Under pressure: A qualitative comparative analysis on the factors contributing to the success and failure of cross-border gas pipeline construction in Europe and Turkey - de Jong, Moniek; Haesebrouck, Tim (Energy Strategy Reviews, 2023)
Around 60% of internationally traded gas is shipped through pipelines. In Europe alone, there are around twenty cross-border gas transmission pipelines and new pipelines continue to be proposed. Yet, proposed pipelines often do not make it past the planning stage. Existing research has been unable to find a framework for determining success and failure in cross-border gas pipeline projects’ construction. In this study, a six condition explanatory framework is developed based on an extensive literature review to explain the success or failure of gas pipelines in Europe. These conditions include: support from the involved states, powerful states, the Commission and the US, as well as the number of stakeholders and the technical difficulties (length and onshore/offshore). The study then conducts a Qualitative Comparative Analysis on 21 European gas pipeline projects and finds that support from those involved, powerful member states and the Commission is imperative for the successful construction of gas pipelines in Europe. The absence of these conditions has the opposite effect.
Created from Fastlane, Scopus look-up
Keywords: Europe; Gas pipelines; Megaprojects; Qualitative comparative analysis; Success factors